1992
DOI: 10.1093/oxfordjournals.aje.a116426
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Relating to Ovarian Cancer Risk: Collaborative Analysis of 12 US Case-Control Studies

Abstract: Data from 12 US case-control studies of ovarian cancer, conducted during the period 1956-1986 and representing some 3,000 cases and 10,000 controls, were pooled and reanalyzed. Separate analyses were conducted for four subgroups of the pooled data: invasive epithelial ovarian cancers in white women; epithelial ovarian cancers of low malignant potential in white women, epithelial ovarian cancers in black women, and nonepithelial ovarian cancers. This paper gives a brief description of the participating studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
62
1
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(71 citation statements)
references
References 0 publications
4
62
1
4
Order By: Relevance
“…In this study, late age at first birth was associated with reduced risk, although the effect was observed only in women who had used oral contraceptives and whose ovarian cancer was diagnosed before menopause. A few previous studies (Purdie et al, 1995), including the collaborative analysis of 12 population-based studies (Whittemore et al, 1992) also noted an inverse relationship between age at first birth and risk, but most found no association (for example, Risch et al, 1994), or an increased risk (for example, Negri et al, 1991). In contrast to previous studies (Risch et al, 1994;Salazar-Martinez et al, 1999), we also found a significant association between increasing age at last birth and reduced risk.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In this study, late age at first birth was associated with reduced risk, although the effect was observed only in women who had used oral contraceptives and whose ovarian cancer was diagnosed before menopause. A few previous studies (Purdie et al, 1995), including the collaborative analysis of 12 population-based studies (Whittemore et al, 1992) also noted an inverse relationship between age at first birth and risk, but most found no association (for example, Risch et al, 1994), or an increased risk (for example, Negri et al, 1991). In contrast to previous studies (Risch et al, 1994;Salazar-Martinez et al, 1999), we also found a significant association between increasing age at last birth and reduced risk.…”
Section: Discussioncontrasting
confidence: 93%
“…In this study, consistent with most previous studies (for example, Franceschi et al, 1991;Chen et al, 1992;Whittemore et al, 1992;Hankinson et al, 1995;Purdie et al, 1995;Salazar-Martinez, 1999), menarcheal age was unrelated to risk overall. However, our findings indicated that increasing age at menarche was associated with reduced risk among premenopausal women; similarly, at least two previous studies have found a stronger association between late menarcheal age and reduced risk among younger women (Parazzini et al, 1989;Whittemore, 1993).…”
Section: Discussionsupporting
confidence: 92%
“…However, this explanation seems inadequate, as the magnitude of the protection afforded by a single pregnancy is disproportionally greater than that which would be expected from the number of ovulations which are avoided during gestation. Even with subsequent lactation amenorrhea, the number of ovulations avoided by one pregnancy progressing to term is no more than 12 to 15, which is less than 5% of the ovulations experienced by a normally ovulatory woman during a reproductive lifetime, yet the protective effect of a single gestation is approximately 40% (1). The use of oral contraceptives also confers protection against ovarian epithelial cancer, which may reach 70% in women using these medications for more than 6 years (l).…”
Section: Introduction Hypothesismentioning
confidence: 99%
“…Hyperreactio luteinalis (HL) is the second most common ovarian disorder of pregnancy after luteoma of pregnancy and is characterized by bilateral cystic enlargement of ovaries (1). The ovaries may be moderately to massively enlarged by multiple luteinized follicle cysts, secondary to stimulation with hCG and gonadotropins (2).…”
Section: Introductionmentioning
confidence: 99%
“…One recent issue that has increased the stress associated with infertility is the potential association between fertility drugs and ovarian cancer (7). It is beyond the scope of this article to address the merit or need for such concern.…”
mentioning
confidence: 99%